1994
DOI: 10.1111/j.1574-6976.1994.tb00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Biology of polyphosphate-accumulating bacteria involved in enhanced biological phosphorus removal

Abstract: Recent research on the process of biological phosphorus removal in lab-scale treatment systems has indicated that: (i) the development of an actively polyP-accumulating bacterial community after the introduction of an anaerobic period may take at least 4 months; (ii) up to 80% of all aerobic bacteria isolated from these communities are able to accumulate polyP; (iii) polyP synthesized by the bacterial communities of lab-scale treatment systems is probably mainly low polymeric, not exceeding 20 P-residues, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(14 citation statements)
references
References 106 publications
0
13
0
1
Order By: Relevance
“…Eutrophication, known as excessive microbial growth, results in reduced transparency, reduced photosynthetic activity, depletion of oxygen, production of toxic compounds and loss of plant and animal species [6]. Korstee and co-authors [7] reported that no eutrophication occurs when the phosphorus concentration is reduced to between 8 µg/L and 10 µg/L, even at nitrogen concentrations of as high as 4 mg/L to 5 mg/L. Generally, municipal wastewater systems are the major sources of phosphorus when compared to other sources of water pollution [8].…”
Section: Introductionmentioning
confidence: 99%
“…Eutrophication, known as excessive microbial growth, results in reduced transparency, reduced photosynthetic activity, depletion of oxygen, production of toxic compounds and loss of plant and animal species [6]. Korstee and co-authors [7] reported that no eutrophication occurs when the phosphorus concentration is reduced to between 8 µg/L and 10 µg/L, even at nitrogen concentrations of as high as 4 mg/L to 5 mg/L. Generally, municipal wastewater systems are the major sources of phosphorus when compared to other sources of water pollution [8].…”
Section: Introductionmentioning
confidence: 99%
“…Eutrophication is a global problem, in which blooms of cyanobacteria and eukaryotic algae occur as a consequence of the breakdown of community homeostasis from continued pollution of oligotrophic aquatic bodies with nutrients like nitrogen (N) and phosphorus (P) at levels which exceed growth-limiting concentrations for these photosynthetic organisms [1,2]. Of these nutrients, P input is considered more critical [3,4] since many of the cyanobacteria are diazotrophic, capable of satisfying their N requirements from ¢xation of atmospheric N 2 . The problems caused by eutrophication have been discussed frequently in the literature, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence points to wastewater treatment plants as major point sources for both N and P, which in the latter case originates from fecal material, industrial and commercial sources and synthetic detergents and other cleaning products [5]. Conventional activated sludge plants designed principally to remove organic carbona-ceous material produce treated e¥uents with high residual P levels, although some N removal does occur in these systems [3,6,11]. In the past 30 years many plants have been designed and built around the world to deliberately reduce not just organic carbon and N levels but also P, using microbially based methods [11^14].…”
Section: Introductionmentioning
confidence: 99%
“…The P requirements by the microbial community are also likely to be high during the transition to aerobic conditions due to the availability of O 2 as an energetically efficient electron acceptor and fermentation products (SCFA), further decreasing the probability of polyphosphate accumulation. Additionally, polyphosphate accumulation and release has shown to be inhibited by denitrification and sulfate reduction due to competition for SCFA (Kortstee et al, 1994;Yamamoto-Ikemoto et al, 1994).…”
Section: P Nmrmentioning
confidence: 99%